Comparação de compósitos de fibra de carbono e resina epóxi processados por moldagem por transferência de resina e moldagem por compressão - Santos, Ana Carolina Mendes Quintanilha Silva [UNESP] (2018)
Composites are considered a class of synergic material by using two or more different constituents in order to obtain a final product in which properties are impossible to obtain using only one of the components. The choice of the processing type and parameters to accomplish it are the main factors in a project development, aiming in an appropriate impregnation, ease and speed of processing. This work has been developed for comparative purposes in relation to the processing of carbon fiber reinforcement composite wrapped by an epoxy resin matrix processed by Resin Transfer Moulding (RTM) and Compression Moulding (CM) techniques. Before processing them, it was needed kinetic and rheological tests by TGA, dual scan and isothermal DSC and Brooksfield viscosimetry to determine the ideal conditions for processing. After their manufacturing, specimens of each technique were submitted to mechanical tests by Interlaminar Shear Stress (ILSS) and after the failure, it was aimed the quantitably and qualitatively analysis, through the microscopy, the conditions that have led to quality each processing. By the results analysis of mechanical test, CM specimens presented on average a decrease of 27% on mechanichal properties by the values of shear stress and, through microscopy analysis, it was observed the presence of macro-porosity that induced the connection of delamination, causing speeding up of crack propagation. This failure may have occurred due to the hand layup in CM process, inducing a heterogeneous impregnation. On other hand, RTM specimens presented no macro-porosity in their structure, characterizing an appropriate impregnation of the resin through the fiber. RTM resulted in higher values of shear stress and a low percentage of voids acceptable for aeronautical industries, therefore, it was concluded its suitableness for primary ... (Complete abstract click electronic access below)